HUBUNGAN PROMOSI JABATAN DENGAN SEMANGAT KERJA KARYAWAN BANK NAGARI CABANG KOTA PEKANBARU - Indiana Jones; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Promotion is the displacement of a position to another position and status have a higher responsibility and is usually accompanied by an increase in salaries / wages other. Promotion provides an important role for every employee, even a dream that always look forward, with the promotion of the employees will be motivated to work hard, excited, and perform the work so that the target company would be achieved optimally. As for which is included into the promotion of this research is the level of education, experience, and skill.Morale is doing the job harder so that the work becomes better. Generating employee morale is an attempt to cause the result of higher working again. The factors that affect the morale is attendance rate, job satisfaction, teamwork and discipline.Bank Nagari is one of the industry engaged in banking services areas of West Sumatra, to be able to realize the objectives of the company should need to improve Human Resources, one of the business by implementing a promotion for employees, employees who are promoted must meet the criteria established by the company, with the holding of this promotion will spur employees to work with the better because it will be well motivated and eager to workBased on the analysis of this study showed that there is a strong relationship between the promotion with employee morale Pekanbaru City Branch of Bank Nagari. It can be seen from the analysis of known data from the t (4.586)> t table (2,055) and Sig (0,000) <0.05. Then hypothesized that there is a connection with the promotion of employee morale is acceptable.Keyword: Job Promotion, Employee Morale